Efficacy of cilostazol on platelet reactivity and cardiovascular outcomes in patients undergoing percutaneous coronary intervention: insights from a meta-analysis of randomised trials. Issue 1 (7th August 2014) - Bangalore, Sripal; Singh, Amita; Toklu, Bora; DiNicolantonio, James J; Croce, Kevin; Feit, Frederick; Bhatt, Deepak L
Abstract : Background: Cilostazol overcomes high on-treatment platelet reactivity (HTPR) and reduces adverse cardiovascular (CV) outcomes after percutaneous coronary intervention (PCI). However, the role for triple antiplatelet therapy (TAPT) with cilostazol in addition to aspirin and clopidogrel after PCI is not well defined. Methods: We conducted a MEDLINE/EMBASE/CENTRAL search for randomised trials, until May 2014, evaluating TAPT compared with dual antiplatelet therapy (DAPT) of aspirin and clopidogrel alone in patients undergoing PCI and reporting platelet reactivity and/or CV outcomes. The primary platelet reactivity outcome was differences in platelet reactivity unit (PRU) with secondary outcomes of %platelet inhibition and rate of HTPR. The primary CV outcome was major adverse cardiovascular events (MACE), with secondary outcomes of death, cardiovascular death, myocardial infarction, stent thrombosis (ST), target lesion revascularisation (TLR) and target vessel revascularisation (TVR) as well as safety outcomes of bleeding and drug discontinuations. Results: In 17 trials that evaluated platelet reactivity outcomes, the mean PRU value was 47.73 units lower with TAPT versus DAPT (95% CI −61.41 to −34.04, p<0.0001; mean PRU 182.90 vs 232.65). TAPT also increased platelet inhibition by 12.71% (95% CI 10.76 to 14.67, p<0.0001), and led to a 60% reduction in the risk of HTPR (relative risk=0.40; 95% CI 0.30 to 0.53) compared with DAPT. Moreover, among the 34 trials that evaluated CV outcomes, TAPT reduced the risk of MACE (incident rate ratio (IRR)=0.68; 95% CI 0.60 to 0.78), TLR (IRR=0.57; 95% CI 0.44 to 0.73), TVR (IRR=0.69; 95% CI 0.59 to 0.81) and ST (IRR=0.63; 95% CI 0.40 to 0.98) with no difference for other outcomes including bleeding, even in trials using drug-eluting stents. Drug discontinuation due to adverse effects was, however, higher with TAPT vs DAPT (IRR=1.59; 95% CI 1.32 to 1.91). Conclusions: In patients undergoing PCI, addition of cilostazol to DAPT results in decreased platelet reactivity and a significant reduction in CV outcomes including ST, even in the drug-eluting stent era.